Pengaruh Religiusitas, Kepercayaan dan Pengetahuan Terhadap Minat Masyarakat Menabung di Bank Syariah Indonesia: Studi Kasus Masyakat Desa Tanjung Sari - Dinda Adela; Maya Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to see the influence of Knowledge, Religiosity and Trust factors on interest in saving in Sharia Banking among the people of Tanjung Sari Village. The sample in this research focused on the people of Tanjung Sari Village who were customers of the Indonesian Sharia Bank, totaling 30 people. The analysis used is multiple linear regression analysis with the help of SPSS. Based on this research, the results of the analysis show that there is a positive influence between the Religiosity variable on Interest in Saving at Indonesian Sharia banks. In the research results above it is explained that the resulting significant value is 0.000 < 0.05, which means a person's level of religiosity also influences interest in saving at the bank. Indonesian Sharia. The results of the analysis show that there is a positive influence between the Trust variable on interest in saving at Indonesian Sharia banks among the people of Tanjung Sari Village. In the research results above, it is explained that the resulting significant value is 0.000 < 0.05, which means that a person's level of trust influences a person's interest in saving at a sharia bank. And the analysis shows that knowledge, religiosity and trust together (simultaneously) have a positive effect on interest in saving at Islamic banks. This is shown by the results of the F test which obtained a sig value of. 0.000 < 0.05 from this value, it can be seen that the Fcount value is greater than Ftable, which means that the variables Knowledge, Religiosity and Trust together have a positive effect on Interest in Saving at Bank Syariah.